Legal Aspects of Joint Account Contracts from a Civil Law Perspective - Syafira Nurrin Qolbisyah; Hardian Iskandar (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the legal validity of agreements and the liability of rekber service providers to their consumers. The research method used is normative juridical with a descriptive analytical approach to the applicable legal regulations related to sales transactions using rekber, supplemented with a limited empirical approach. In the Joint Account system, buyers are required to transfer funds, which is considered as acceptance of the applicable terms and conditions. Violation of these terms results in the forfeiture of the fees that have been paid. Novelty of this study lies in the agreement of sale and purchase and the use of a Joint Account system as a third party. The results of the study indicate that agreements in Joint Account transactions have binding force as contracts between sellers and buyers. However, there is the potential for legal cancellation of the agreement if the terms and conditions are considered unfair, non-transparent, or detrimental to consumers. Conclusion This study identifies that agreements in sales transactions using Joint Account systems such as Shopee are considered valid if they comply with the provisions of the Civil Code and there are two alternative dispute resolution methods in the event of breach of contract or fraud, namely non-litigation efforts through mediation and negotiation or with the assistance of a third party, or litigation through the court system.